Extensive functional evaluations to monitor aerobic training in Becker Muscular Dystrophy: A case report - Caterina Tramonti; Bruno Rossi; Carmelo Chisari (PAGEPress Publications, 2016)
Low-intensity aerobic training seems to have positive effects on muscle strength, endurance and fatigue in Becker Muscular Dystrophy (BMD) patients. We describe the case of a 33-year old BMD man, who performed a four-week aerobic training. Extensive functional evaluations were executed to monitor the efficacy of the rehabilitative treatment. Results evidenced an increased force exertion and an improvement in muscle contraction during sustained exercise. An improvement of walk velocity, together with agility, endurance capacity and oxygen consumption during exercise was observed. Moreover, an enhanced metabolic efficiency was evidenced, as shown by reduced lactate blood levels after training. Interestingly, CK showed higher levels after the training protocol, revealing possible muscle damage. In conclusion, aerobic training may represent an effective method improving exercise performance, functional status and metabolic efficiency. Anyway, a careful functional assessment should be taken into account as a useful approach in the management of the disease's rehabilitative treatment.